Association Between Childhood Maltreatment and Symptoms of Obsessive-Compulsive Disorder: A Meta-Analysis - Ou, Wenwen; Li, Zhijun; Zheng, Qi; Chen, Wentao; Liu, Jin; Liu, Bangshan; Zhang, Yan (Frontiers in Psychiatry, 2021)
Background: Previous studies have indicated that childhood maltreatment (CM) may potentially influence the clinical symptomatology of obsessive-compulsive disorder (OCD). Here, we aimed to quantify the relationship between CM and obsessive-compulsive symptoms (OCS) and depressive symptoms in OCD through a meta-analysis. Method: We searched PubMed, Embase, Cochrane Library, and PsycARTICLES databases for articles reporting the association between CM and OCD on April 15, 2020. Random-effect models were used to quantify the relationship between CM and the severity of OCS and depressive symptoms in OCD. Results: Ten records with 1,611 OCD patients were included in the meta-analysis. The results revealed that CM is positively correlated with the severity of OCS [r = 0.10, 95%Confidence Interval (CI): 0.01–0.19, P = 0.04] as well as depressive symptoms in OCD (r = 0.15, 95%CI: 0.07–0.24, P = 0.0002). For the subtypes of CM, childhood emotional abuse (CEA) and childhood sexual abuse (CSA) was related with the severity of OCS (r = 0.11, 95%CI: 0.03–0.19, P = 0.009) and obsession (r = 0.13, 95%CI: 0.03–0.23, P = 0.01), respectively. Conclusion: Our meta-analysis indicates that OCD patients who suffered more CM may exhibit more severe OCS and depressive symptoms.